Антология выдающихся достижений в науке и технике. Часть 50: конструктор ракетно - космической техники Вернер фон Браун и его свершения в ракетостроении - Баранов, Михаил Иванович (Национальный технический университет "Харьковский политехнический институт", 2019)
Приведен краткий научно-исторический очерк о выдающемся немецко-американском конструкторе ракетно-космической техники Вернере фон Брауне, ставшем одним из основоположников мирового ракетостроения. Описаны основные научно-технические достижения Вернера фон Брауна в области современного ракетостроения, перебравшегося по настойчивой инициативе американских спецслужб после разгрома Германии во Второй мировой войне в США (1945 г.) для продолжения работы в области ракетной техники, носящей военно-стратегический характер. Показано, что Вернер фон Браун является основателем космической программы США и руководителем разработок американских космических кораблей«Аполлон». Под его научно-техническим руководством в США были созданы мощные ракетоносители серии «Редстоун» и«Сатурн», благодаря которым на околоземную орбиту был запущен первый искусственный спутник США «Эксплорер-1» (1958 г.), а американский астронавт впервые в истории человечества ступил на поверхность Луны (1969 г.).

Purpose. Preparation of short scientifically-historical essay about one of founders of world rocket production, distinguished German-American designer of modern space-rocket technique Wernher von Braun. Methodology.Known scientific methods of collection, analysis and analytical treatment of scientific and technical information, touching becoming and development in the world of space-rocket technique and resulted in scientific monographs, journals and internetreports. Results. A short scientifically-historical essay is presented about the distin-guished German-American designerof space-rocket technique Wernher von Braun, becoming one of founders of world rocket production. Basic scientific and technical achievements of talented and purposeful scientist Doctor of Physics Wernher von Braun in area of modern rocket production, getting over on persistent initiative of the American special services after the defeat of Germany in World War II in the USA (1945) for con-tinuation of the work in area of missile technology (he was the main designer of the German battle ballistic rocket V-2 of midrange with a liquid rocket engine (LRE), created in 1944), carrying military-strategic character bythat time. It is shown that Wernher von Braun is the founder of the space program of the USA and leader of developments of the American pilot-controlled spaceships of series «Apollo» within the framework of the Lunar program of the USA.It is marked that under scientific and technical guidance of Wernher von Braun in the USA powerful launch vehicles were created with LRE of battle series «Redstone» of midrange (1958, military index of PGM-11) and space series «Saturn» (1969), due to which on a circumter-restrial orbit the first artificial satellite of the USA «Explorer-1» launched (31 January, 1958), and the American astronaut Neil Armstrong first in history of humanity stepped on the surface of the Moon (20 July, 1969). Originality. Certain systematization is executed known from mass media of scientific and technical materials, touching becoming and development in 20-th century of world rocket production, at the sources of which the talented scientist Doctor of Physics and distinguished German-American designer of space-rocket technique Wernher von Braun. Practіcal value.Scientific popularization and deepening for the students of higher school, engineerand technical and scientific workers of physical and technical knowledge in area of world history of becoming and development of modern rocket production, extending their scientific and technical range of interests and further development of scientific and technical progress in society.
An anthology of the distinguished achievements in science and technique. Part 50: Rocket-space technology designer Wernher von Braun and his accomplishments in missile design
Keywords: ракетно-космическая техника; научно-исторический очерк; space-rocket technique; scientifically-historical essay